Tongxinluo attenuates atherosclerosis by inhibiting ROS/NLRP3/caspase-1-mediated endothelial cell pyroptosis. (25th March 2023) - Jiang, Xuejiao; Ma, Chongyang; Gao, Yanbin; Cui, Hehe; Zheng, Yalin; Li, JinXia; Zong, Wenjing; Zhang, Qiuyun
Abstract: Ethnopharmacological relevance: Tongxinluo (TXL) is one of the most common traditional Chinese medicines and plays a vital role in treating atherosclerosis (AS). Endothelial cell (EC) pyroptosis plays a crucial role in the development of AS. Previous research revealed the inhibitory function of TXL in EC apoptosis and autophagy. However, whether TXL can inhibit the pyroptosis of ECs has not been determined. Aim of the study: To explore the influence of TXL on EC pyroptosis and determine its underlying mechanism of action in AS. Materials and methods: The TXL components were determined by ultra-performance liquid chromatography coupled with a photodiode array detector. We used ApoE −/− mice to establish a disease model of AS. After treatment with TXL, we recorded pathological changes in the mice and performed immunofluorescence staining of mice aortas. We also measured protein and gene levels to explore the influence of TXL on pyroptosis in vivo . The model was established by stimulating mouse aortic endothelial cells (MAECs) with oxidized low-density lipoprotein (ox-LDL) and analyzing the effect of TXL on pyroptosis by Western blotting (WB), real-time PCR (RT-PCR), and flow cytometry (FCM). We also investigated the impact of TXL on reactive oxygen species (ROS) by FCM and WB. Results: Ten major components of TXL were detected. The vivo results showed that TXL inhibited the development of AS and decreased EC pyroptosis, the activation of caspase-1, and the release of inflammatory cytokines. The vitro experiments showed that TXL significantly reduced the extent of injury to MAECs by oxidized LDL (ox-LDL). TXL reversed the high expression of gasdermin D and other proteins induced by ox-LDL and had a significant synergistic effect with the caspase-1 inhibitor VX-765. We also confirmed that TXL decreased the accumulation of ROS and the expression levels of its essential regulatory proteins Cox2 and iNOS. When ROS accumulation was reduced, EC pyroptotic damage was reduced accordingly. Conclusion: Our results indicated that TXL inhibited EC pyroptosis in AS. Reducing the accumulation of ROS may be the essential mechanism of AS inhibition by TXL. Graphical abstract: Image 1 Highlights: Tongxinluo (TXL) delayed the development of atherosclerosis (AS). TXL inhibited endothelial cell pyroptosis during the development of AS. TXL inhibited endothelial cell pyroptosis by reducing the accumulation of ROS.